Comparative study of the effectiveness of three learning environments: Hyper-realistic virtual simulations, traditional schematic simulations and traditional laboratory - Guadalupe Martínez; Francisco L. Naranjo; Ángel L. Pérez; Maria Isabel Suero; Pedro J. Pardo (Physical Review Special Topics. Physics Education Research, 2011)
This study compared the educational effects of computer simulations developed in a hyper-realistic virtual environment with the educational effects of either traditional schematic simulations or a traditional optics laboratory. The virtual environment was constructed on the basis of Java applets complemented with a photorealistic visual output. This new virtual environment concept, which we call hyper-realistic, transcends basic schematic simulation; it provides the user with a more realistic perception of a physical phenomenon being simulated. We compared the learning achievements of three equivalent, homogeneous groups of undergraduates—an experimental group who used only the hyper-realistic virtual laboratory, a first control group who used a schematic simulation, and a second control group who used the traditional laboratory. The three groups received the same theoretical preparation and carried out equivalent practicals in their respective learning environments. The topic chosen for the experiment was optical aberrations. An analysis of variance applied to the data of the study demonstrated a statistically significant difference (p value <0.05) between the three groups. The learning achievements attained by the group using the hyper-realistic virtual environment were 6.1 percentage points higher than those for the group using the traditional schematic simulations and 9.5 percentage points higher than those for the group using the traditional laboratory.